Race andEnvironmental Justice in the Era of Climate Change and COVID-19 (University of Michigan Press, 2025)
Abstract englisch (Max. 3 Sätze) Abstract English* (max. 3 sentences) Informed by the transdisciplinary research in social and environmental justice, Race and Environmental Justice in the Era of Climate Change and COVID-19 is both a scholarly contribution to the ongoing discourse and a form of activism for environmental, climate, and health justice. Using race and indigeneity as an analytical lens, the book explores how justice in the era of climate change and COVID-19 is envisioned, depicted, and achieved, illustrating the wide health and safety gap between individuals, communities, and even nations living under different environmental conditions, but also moving beyond the human toward justice for all. Race and Environmental Justice in the Era of Climate Change and COVID-19 is a scholarly endeavor to foreground the voices from world communities, provide solutions to environmental and health crises, and restore justice for all. Race and Environmental Justice in the Era of Climate Change and COVID-19 ist ein wissenschaftlicher Beitrag zum laufenden Diskurs und eine Form des Aktivismus für Umwelt-, Klima- und Gesundheitsgerechtigkeit, der von der transdisziplinären Forschung im Bereich der sozialen und ökologischen Gerechtigkeit geprägt ist. Unter Verwendung von Ethnie und Indigenität als analytische Linse untersucht das Buch wie Gerechtigkeit im Zeitalter von Klimawandel und COVID-19 gedacht, dargestellt und erreicht wird und veranschaulicht die große Kluft in Bezug auf Gesundheit und Sicherheit zwischen Menschen, Gemeinschaften und sogar Nationen, die unter verschiedenen Umweltbedingungen leben, aber auch über das Menschliche hinaus in Richtung Gerechtigkeit für alle. Race and Environmental Justice in the Era of Climate Change and COVID-19 ist ein wissenschaftliches Unterfangen, das die Stimmen von Weltgemeinschaften in den Vordergrund stellt, Lösungen für Umwelt- und Gesundheitskrisen bietet und Gerechtigkeit für alle wiederherstellt.